Diversity and prevalence of endoparasites in domestic chickens across an elevation gradient (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Setyowati EA, Santoso S, Rokhmani, Rochmatino. 2022. Diversity and prevalence of endoparasites in domestic chickens across an elevation gradient. Biodiversitas 23: 3936-3942. The domestic chicken farm is negatively affected by endoparasites, which decrease immunity, egg production, and body weight. Although these effects are well understood in large-scale chicken farms, here we aimed to understand endoparasite diversity and prevalence in the context of local-scale domestic chicken farms conducted in Central Java, Indonesia, according to elevation. Chickens were sampled from three villages each in two regions; lowland in Banyumas District and highland in Purbalingga. The result showed that the diversity of endoparasite is very low (H' index: 1.3065-1.3773) and we detected only four endoparasite species (Ascaridia galli, Trichuris trichiura, Heterakis gallinarum (Nematoda), and Raillietina sp. (Cestoda) among a sample of 300 chickens. Endoparasite infection was significantly more prevalent in the lowland villages (70%) than in highland (48%,) (p < 0.05). Among endoparasites found, A. galli was the most prevalent species among all samples (50.0±0.0% of infections in the lowlands and 23.7±1.15% in the highlands) the second is H. gallinarum accounted for 38.3±7.64% of all infections in the highlands and 15.3±0.58% in the lowlands. Raillietina sp. accounted for 35.0±5.0% and 7.3±0.58% of all infections, and T. trichiura accounted for 25.0±5.0 % and 16.0±1.0%. The rate of endoparasite infection within the study area is currently moderate and mainly affected by methods of farm, our findings can serve as a baseline for controlling infection in domestic chickens.
Keywords: Ascaridia galli, Cestoda, Heterakis gallinarum, Nematoda, Raillietina, Trichuris trichiura